Preparation method of artificial graphite material and artificial graphite material
By improving the preparation process of phenolic resin and combining vacuum impregnation and isostatic pressure treatment technology, the pores in artificial graphite materials are filled, solving the problem of low performance of porous graphite materials and achieving higher density and performance improvements.
Patent Information
- Application Number
- CN202411809038.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
AI Technical Summary
The porous graphite produced in the existing artificial graphite production process has many pores, resulting in lower tap density and compaction density, and it is difficult to effectively fill pores, which reduces the performance of the material.
By improving the preparation process of phenolic resin, low viscosity and high coking value are prepared, and combined with vacuum impregnation and isostatic pressure treatment technology, the pores in the graphite material are filled, thereby improving the density and performance of the material.
The tap density and compaction density of artificial graphite are significantly improved, the specific surface area is reduced, and the overall performance of the material is improved, especially in the negative electrode material applications of lithium-ion batteries, which show higher energy density and first-time Coulomb efficiency.
Smart Images

Figure BDA0005180067250000181
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy material preparation, and in particular to a preparation method of an artificial graphite material and the artificial graphite material. Background Art
[0002] Lithium-ion batteries have developed rapidly in recent years, and related industries have also developed rapidly, such as new energy vehicles and drones. The negative electrode material of lithium-ion batteries is generally made of graphite. The use of artificial graphite as the negative electrode of lithium-ion batteries has significant advantages, such as high energy density and rate, low expansion, fast charging capability, high cycle ratio, safety and pollution-free. However, the existing artificial graphite production process will produce some by-products with low tap density and compaction density and high specific surface area, such as resistors in the graphitization process and unqualified products in processing. The above reasons are mostly caused by the large number of pores in the graphite itself. This type of material is called porous graphite.
[0003] At present, porous graphite is generally treated with a carburizer or scrapped, or used as a low-end negative electrode material after simple processing. This method reduces the value of porous graphite. At present, in order to improve its value, the industry has a series of conventional treatments on resistor materials such as rough crushing, crushing, shaping and carbonization. The above treatments only improve its appearance through shaping, which has the effect of improving the tap density and compaction density, but the performance is not greatly improved. Since the characteristics of low compaction density, low tap density and high specific surface area of resistor materials are mainly caused by the large number of pores in resistor materials, some researchers have also used vacuum impregnation to fill the pores of resistor materials. The liquid for conventional vacuum impregnation is mainly composed of asphalt and phenolic resin, and the viscosity of asphalt and phenolic resin is relatively high, and it is difficult to enter the pores. In addition, the volatile matter in general asphalt and phenolic resin is relatively high. In the carbonization process, as the volatile matter in asphalt and phenolic resin runs out, the pore filling effect is poor. Therefore, it is necessary to provide a method to improve the defects of vacuum impregnation, so as to better reduce the pores in the porous graphite product to obtain artificial graphite with better performance. Summary of the invention
[0004] In view of the above problems, the purpose of the present invention is to provide a method for preparing an artificial graphite material and an artificial graphite material. The preparation method can better fill the pores in the porous graphite with the phenolic resin by preparing a phenolic resin that is easy to impregnate, improving the impregnation process and post-process treatment, thereby better improving the compacted density, tap density and specific surface area of the artificial graphite material.
[0005] To achieve the above object, the first aspect of the present invention provides a method for preparing an artificial graphite material, comprising the steps of:
[0006] (I) Pretreatment of porous graphite
[0007] The porous graphite is crushed and shaped to obtain a graphite matrix;
[0008] (II) Preparation of phenolic resin
[0009] Phenol and an organic base are mixed and heated, formaldehyde is added dropwise for reaction, and an inorganic base is added for further reaction to obtain a phenolic resin;
[0010] (III) Impregnation
[0011] Under vacuum conditions, the graphite substrate is impregnated with the phenolic resin and stirred under pressure for a certain period of time, and then heated to remove volatile components of the resin to obtain a precursor;
[0012] (IV) Carbonization
[0013] Carbonizing the precursor to obtain a primary material;
[0014] (V) Isostatic Pressing
[0015] The initial material is subjected to isostatic pressing and then to post-treatment.
[0016] The preparation method of the present invention has at least the following technical effects.
[0017] (1) After the porous graphite is crushed and shaped, the surface burrs of the porous graphite can be reduced to increase the tap density of the graphite matrix.
[0018] (2) After the phenolic resin is impregnated into the graphite matrix, pressurization and heating are applied to not only remove the volatile components of the resin, but also allow the phenolic resin to fill the internal pores of the porous graphite and solidify. After carbonization, isostatic pressing technology is used to compress the internal pores of the porous graphite, thereby increasing the tap density and compaction density.
[0019] (3) Mixing phenol and organic base and adding formaldehyde dropwise during heating can make the reaction of formaldehyde and phenol more thorough, and more hydroxymethylphenol oligomers are generated in the early stage of the addition. In the later stage, the number average molecular weight of the phenolic resin finally synthesized is small due to the large number of oligomer molecules, so the generated phenolic resin will have a lower viscosity. In addition, in the early stage, the organic base is used for catalytic reaction. Since the basicity of the organic base is weak and the catalytic ability is weak, the rapid increase of the molecular weight in the early stage can be further prevented. After the formaldehyde is added dropwise, an inorganic base is added for secondary catalysis. The secondary catalysis can form high ortho-position benzene rings to increase the cross-linking degree of the molecules, thereby increasing the coking value of the phenolic resin. Therefore, in this preparation method, a phenolic resin with low viscosity and high coking value (viscosity at room temperature ≤400mPa.s, coking value ≥66%) can be obtained through the combination of the dropwise addition reaction of formaldehyde, organic base and inorganic base. The low viscosity of the phenolic resin ensures that the phenolic resin can more easily enter the pores of the porous graphite under vacuum conditions, and the higher coking value ensures that the phenolic resin that enters the pores of the porous graphite has more solid parts retained in the pores after heating, thereby filling more pores to reduce the specific surface area of the porous graphite and increase the compacted density and tap density of the porous graphite.
[0020] (4) First, the phenolic resin is impregnated into the graphite substrate under vacuum conditions. After the liquid phenolic resin completely infiltrates the graphite substrate, pressure is applied. Excess phenolic resin will be discharged under pressure. When the high pressure is maintained unchanged after the pressure is applied, the high pressure at this time directly acts on the phenolic resin bonded to the surface of the graphite substrate due to the discharge of excess liquid resin, which is beneficial to the impregnation of the liquid phenolic resin. In addition, the stirring process can effectively increase the contact between the graphite substrate and the surface of the phenolic resin, which is beneficial to accelerate the further impregnation of the liquid phenolic resin.
[0021] Therefore, the present invention improves the preparation process of phenolic resin to obtain phenolic resin with low viscosity and high coking value, and then combines vacuum impregnation process and isostatic pressing to better fill the pores in porous graphite, thereby better improving the compacted density, tap density and specific surface area of graphite.
[0022] In some embodiments, the total pore volume of the porous graphite is 0.01 to 0.10 cm 3 / g, micropore volume is 0.0005~0.010cm 3 / g, the micropore volume accounts for 0.5-10.0%, the particle size is 3-8cm, and the graphitization degree is 90-95%.
[0023] In some embodiments, the specific surface area of the porous graphite is greater than 12.0 m 2 / g, tap density is 0.65~0.75g / cm 3 , compacted density ≤1.65g / cm3 , the first coulombic efficiency is ≤85%.
[0024] In some embodiments, the pulverization includes coarse pulverization and fine pulverization, firstly coarse pulverization to a particle size of 1 to 100 mm, and then fine pulverization to a particle size of 10 to 15 μm.
[0025] In some embodiments, the pulverization includes coarse crushing and fine crushing. The coarse crushing is carried out using a jaw crusher, and the fine crushing is carried out using a mechanical mill, a roller mill or a jet mill.
[0026] In some implementation schemes, the main machine frequency of the shaping machine used for the shaping is 2 to 5 Hz, and the main machine graded frequency is 5 to 7 Hz.
[0027] In some embodiments, the organic base includes at least one of ethylenediamine, triethylamine, and triethanolamine.
[0028] In some embodiments, the organic base accounts for 1-5% of the mass of the phenol.
[0029] In some embodiments, the heating temperature in step (II) is 50-100°C.
[0030] In some embodiments, the molar ratio of the formaldehyde to the phenol is 1.0 to 1.4:1.
[0031] In some embodiments, the inorganic base comprises potassium hydroxide and / or sodium hydroxide.
[0032] In some embodiments, the inorganic base accounts for 1-5% of the mass of the phenol.
[0033] In some embodiments, the phenol and the organic base are stirred in a magnetic stirring water bath, and the stirring time is 15 to 40 minutes.
[0034] In some embodiments, the inorganic base is stirred after being added, and the stirring time is 0.5 to 2.0 hours.
[0035] In some embodiments, the phenolic resin has a viscosity of ≤400 mPa.s at room temperature and a coking value of ≥66%.
[0036] In some embodiments, the maximum temperature of the heating in step (III) is 500-800°C.
[0037] In some embodiments, the heating in step (III) is step heating, and the step heating is first heated to 200-400°C at a rate of 2-8°C / min and then kept warm for 1-4 hours, and then heated to 500-800°C at a rate of 2-5°C / min and then kept warm for 3-10 hours.
[0038] In some embodiments, the carbonization temperature is 1000-1300°C.
[0039] In some embodiments, the carbonization is gradient carbonization, and the gradient carbonization is first heated to 200-400°C at a rate of 8-15°C / min and then kept warm for 1.0-4.0h, then heated to 800-1000°C at a rate of 2-8°C / min and then kept warm for 0.5-2.0h, and finally heated to 1050-1200°C at a rate of 1-5°C / min and then kept warm for 1.0-5.0h.
[0040] In some embodiments, the pressure used in the isostatic pressing treatment is 100-170 MPa.
[0041] In some embodiments, the post-processing includes breaking up, demagnetizing and screening.
[0042] In some embodiments, before the phenolic resin is impregnated into the graphite substrate, the phenolic resin and an anionic surfactant are mixed to obtain micellar phenolic resin.
[0043] In some embodiments, the anionic surfactant includes at least one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfonate, sodium dodecyl sulfate and sodium hexadecyl sulfonate, and the mass ratio of the anionic surfactant to the phenolic resin is 1:800-1200.
[0044] In some embodiments, the micellar phenolic resin has a viscosity of ≤200 mPa.s at room temperature and a coking value of ≥66%.
[0045] In some embodiments, before the graphite substrate is impregnated with the phenolic resin, the graphite substrate is placed in an impregnation tank and vacuum is applied to exhaust air in the pores of the graphite substrate.
[0046] In some embodiments, the vacuum is evacuated to a pressure of ≤-0.08 MPa, and the pressure is maintained for 0.5 to 1.0 h.
[0047] In some embodiments, the phenolic resin and the graphite matrix are impregnated in a kneader.
[0048] In some embodiments, the kneader is first pressurized to 3-8 MPa, then the pressurization is stopped and the pressure is maintained constant while stirring for 0.5-3.0 h.
[0049] In some embodiments, the frequency of the kneader is 10 to 20 Hz.
[0050] The second aspect of the present invention provides an artificial graphite material with a specific surface area of 1.6 m 2 / g, tap density is 0.95~1.10g / cm 3 , compacted density is 1.70~1.86g / cm 3 , the first coulombic efficiency is ≥92%. DETAILED DESCRIPTION
[0051] The artificial graphite material of the present invention can be used alone or mixed with other negative electrode active materials (such as natural graphite, silicon-oxygen materials, silicon-carbon materials, soft carbon and / or hard carbon, etc.). The artificial graphite material can be applied to secondary batteries, which include positive electrode active materials and negative electrode active materials. The positive electrode active material includes at least one of a lithium cobalt oxide positive electrode material, a lithium iron phosphate positive electrode material, a nickel cobalt manganese oxide positive electrode material, and a nickel cobalt aluminum oxide positive electrode material.
[0052] The first coulombic efficiency of the artificial graphite material of the present invention is ≥92%, and as an example, it can be but not limited to ≥92%, ≥93%, ≥94%. The tap density of the artificial graphite material is 0.95-1.10 g / cm 3 , as an example, it can be but not limited to 0.95 g / cm 3 , 0.96g / cm 3 , 0.97g / cm 3 、0.98g / cm 3 , 0.99g / cm 3 , 1.00g / cm 3 , 1.01g / cm 3 , 1.02g / cm 3 , 1.03g / cm 3 , 1.04g / cm 3 , 1.05g / cm 3 , 1.06g / cm 3 , 1.07g / cm 3 , 1.08g / cm 3 , 1.09g / cm 3 , 1.10g / cm 3 The compacted density of artificial graphite material is 1.70~1.86g / cm 3 , as an example, it can be but not limited to 1.70 g / cm 3 , 1.71g / cm 3 , 1.72g / cm 3 、1.73g / cm 3 , 1.74g / cm 3 , 1.75g / cm 3 , 1.76g / cm 3 , 1.77g / cm 3 , 1.78g / cm 3, 1.79g / cm 3 , 1.80g / cm 3 、1.81g / cm 3 , 1.82g / cm 3 , 1.83g / cm 3 , 1.84g / cm 3 , 1.85g / cm 3 , 1.86g / cm 3 The specific surface area of artificial graphite material is ≤1.6m 2 / g, as an example, it can be but not limited to 1.6m 2 / g, 1.5m 2 / g, 1.4m 2 / g, 1.3m 2 / g, 1.2m 2 / g, 1.1m 2 / g, 1.0m 2 / g.
[0053] The method for preparing the artificial graphite material of the present invention may include the steps of:
[0054] (I) Pretreatment of porous graphite
[0055] The porous graphite is crushed and shaped to obtain a graphite matrix;
[0056] (II) Preparation of phenolic resin
[0057] Phenol and an organic base are mixed and heated, formaldehyde is added dropwise for reaction, and an inorganic base is added for further reaction to obtain a phenolic resin;
[0058] (III) Impregnation
[0059] Under vacuum conditions, a phenolic resin is impregnated into a graphite substrate and stirred under pressure for a certain period of time, and then heated to remove volatile components of the resin to obtain a precursor;
[0060] (IV) Carbonization
[0061] Carbonizing the precursor to obtain a primary material;
[0062] (V) Isostatic Pressing
[0063] The primary material is subjected to isostatic pressing and then post-processing.
[0064] Wherein, in step (I), the total pore volume of the porous graphite is 0.01 to 0.10 cm 3 / g, as an example, it can be but not limited to 0.01cm 3 / g, 0.02cm 3 / g, 0.03cm 3 / g, 0.04cm 3 / g, 0.05cm 3 / g, 0.06cm 3 / g, 0.07cm 3 / g, 0.08cm 3 / g, 0.09cm 3 / g, 0.010cm 3 / g. The micropore volume is 0.0005~0.010cm 3 / g, as an example, it can be but not limited to 0.0005cm 3 / g, 0.0006cm 3 / g, 0.0007cm 3 / g, 0.0008cm 3 / g, 0.0009cm 3 / g, 0.010cm 3 / g. The micropore volume accounts for 0.5-10.0%, and as an example, it can be, but not limited to, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 10.0%. The particle size is 3-8cm, and as an example, it can be, but not limited to, 3cm, 4cm, 5cm, 6cm, 7cm, 8cm. The degree of graphitization is 90-95%, and as an example, it can be, but not limited to, 90%, 91%, 92%, 93%, 94%, 95%. Porous graphite has a certain pore structure, so it is easy to impregnate liquid phenolic resin.
[0065] The specific surface area of porous graphite is >12.0m 2 / g, as an example, it can be but not limited to 12.5m 2 / g, 13.0m 2 / g, 13.5m 2 / g, 14.0m 2 / g, 14.5m 2 / g, 15.0m 2 / g, 15.5m 2 / g. The tap density of porous graphite is 0.65~0.75g / cm 3 , as an example, it can be but not limited to 0.65 g / cm 3 , 0.66g / cm 3 , 0.67g / cm 3 , 0.68g / cm 3 , 0.69g / cm 3 、0.70g / cm 3, 0.71g / cm 3 , 0.72g / cm 3 , 0.73 / cm 3 , 0.74g / cm 3 , 0.75g / cm 3 The compacted density of porous graphite is ≤1.65g / cm 3 , as an example, it can be but not limited to 1.65 g / cm 3 , 1.64g / cm 3 、1.63g / cm 3 、1.62g / cm 3 , 1.61g / cm 3 , 1.60g / cm 3 , 1.59g / cm 3 , 1.58g / cm 3 , 1.57g / cm 3 , 1.56g / cm 3 , 1.55g / cm 3 , 1.54g / cm 3 , 1.53g / cm 3 , 1.52g / cm 3 , 1.51g / cm 3 , 1.50g / cm 3 The first coulomb efficiency is ≤85%, which can be, but not limited to, 85%, 84%, 83%, 82%, 81%, and 80% as an example. After the artificial graphite material is prepared from porous graphite as a raw material, the tap density ranges from 0.65 to 0.75 g / cm 3 Increase to 0.95~1.10g / cm 3 , compacted density from ≤1.65g / cm 3 Increased to 1.70~1.86g / cm 3 , which can more effectively improve the energy density of the battery. The filling of phenolic resin reduces the pores and can increase the specific surface area from >12.0m 2 / g reduced to 1.6m 2 / g or less, further reducing the formation of SEI film during charging and discharging, and increasing the battery's first coulombic efficiency from ≤85% to over 92%.
[0066] The pulverization of porous graphite includes coarse crushing and fine crushing, first coarse crushing to a particle size of 1 to 100 mm, and then fine crushing to a particle size of 10 to 15 μm. The equipment used for coarse crushing is a jaw crusher, and the equipment used for fine crushing is a mechanical mill, a roller mill or an air flow mill. The main machine frequency of the shaping machine used for shaping is 2 to 5 Hz, and the main machine classification frequency is 5 to 7 Hz. As an example, the main machine frequency can be but not limited to 2 Hz, 3 Hz, 4 Hz, 5 Hz, and the main machine classification frequency can be but not limited to 5 Hz, 6 Hz, 7 Hz. Shaping can improve the material morphology, reduce the burrs on the surface of the material, and further improve the material's tap density and compaction density.
[0067] In step (II), the organic base includes at least one of ethylenediamine, triethylamine and triethanolamine. The organic base accounts for 1-5% of the mass of phenol. As an example, the proportion of the organic base can be but not limited to 1%, 2%, 3%, 4%, 5%. The organic base is a catalyst for the early reaction, and its alkalinity is weak, and its catalytic ability is weak, which can prevent the rapid increase of the molecular weight in the early reaction.
[0068] The inorganic base includes potassium hydroxide and / or sodium hydroxide. The inorganic base accounts for 1-5% of the mass of phenol. As an example, the proportion of the inorganic base can be, but is not limited to, 1%, 2%, 3%, 4%, and 5%. The inorganic base acts as a catalyst for the later reaction and can perform secondary catalysis. The secondary catalysis can form high ortho-position benzene rings to increase the cross-linking degree of the molecule, thereby increasing the coking value of the phenolic resin.
[0069] The molar ratio of formaldehyde to phenol is 1.0 to 1.4:1. For example, the molar ratio may be, but is not limited to, 1.0:1, 1.1:1, 1.2:1, 1.3:1, and 1.4:1. The reaction of formaldehyde and phenol can generate phenolic resin, and formaldehyde is added by dropwise addition. During the stirring process, the formaldehyde reaction can be more thorough. More hydroxymethylphenol oligomers are generated in the early stage of dropwise addition. In the later stage, due to the large number of oligomer molecules, the number average molecular weight of the finally synthesized phenolic resin is small, so it has a lower viscosity. The viscosity of the prepared phenolic resin at room temperature is ≤400mPa.s, and the coking value is ≥66%. As an example, the viscosity can be, but not limited to, 400mPa.s, 390mPa.s, 380mPa.s, 370mPa.s, 360mPa.s, 350mPa.s, 340mPa.s, 330mPa.s, 320mPa.s, and 310mPa.s. The coking value is ≥66%. As an example, the coking value can be, but not limited to, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, and 75%.
[0070] The heating temperature of phenol and organic base is 50-100°C. As an example, the heating temperature can be, but not limited to, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, and 100°C. Phenol and organic base are stirred in a magnetic stirring water bath, and the stirring time is 15-40min. As an example, the stirring time can be, but not limited to, 15min, 20min, 25min, 30min, 35min, and 40min. After the inorganic base is added, stirring is performed, and the stirring time is 0.5-2.0h. As an example, the stirring time can be, but not limited to, 0.5h, 1.0h, 1.5h, and 2.0h. A liquid phenolic resin can be obtained by heating and stirring.
[0071] Before the phenolic resin is impregnated into the graphite matrix, the phenolic resin and the anionic surfactant are mixed to obtain a micellar phenolic resin. The anionic surfactant includes at least one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfonate, sodium dodecyl sulfate and sodium hexadecyl sulfonate. The mass ratio of the anionic surfactant to the phenolic resin is 1:800-1200. As an example, the mass ratio of the two is 1:800, 1:850, 1:900, 1:950, 1:1000, 1:1050, 1:1100, 1:1150, 1:1200. When an anionic surfactant is added to the liquid phase phenolic resin, the anionic surfactant will form a micellar structure in the phenolic resin. Such micelles will occupy a certain space in the liquid and produce a steric hindrance effect. The steric hindrance will hinder the mutual approach and entanglement between the phenolic resin molecules, making the flow of the liquid easier, thereby causing the viscosity of the phenolic resin to decrease. The reduction in the viscosity of the phenolic resin will further improve the effect of vacuum impregnation, thereby filling more pores to increase the compacted density and tap density of graphite and reduce the specific surface area of graphite. The viscosity of the micellar phenolic resin at room temperature is ≤200mPa.s. As an example, the viscosity can be but is not limited to 200mPa.s, 195mPa.s, 190mPa.s, 185mPa.s, 180mPa.s, 175mPa.s, 170mPa.s. The coking value is ≥66%. As an example, the coking value can be but is not limited to 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%.
[0072] Before the phenolic resin is impregnated into the graphite substrate, the graphite substrate is placed in an impregnation tank and vacuumed to expel the air in the pores of the graphite substrate. Vacuum and maintain for a period of time to ensure that the air in the graphite substrate is expelled as much as possible. Vacuum to a pressure of ≤-0.08MPa, and maintain the pressure for 0.5 to 1.0h. As an example, the time can be but is not limited to 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1.0h.
[0073] The maximum temperature of heating in step (III) is 500-800°C. As an example, the maximum temperature can be, but is not limited to, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, and 800°C. The heating is step-by-step heating, which is first heated to 200-400°C at a rate of 2-8°C / min and then kept warm for 1-4h, and then heated to 500-800°C at a rate of 2-5°C / min and kept warm for 3-10h. The phenolic resin and the graphite matrix are impregnated in a kneader, and the kneader is first pressurized to 3-8MPa and then stopped and the pressure is kept constant and stirred for 0.5-3.0h. Under vacuum conditions, the prepared phenolic resin is injected into the kneader. When the phenolic resin completely infiltrates the graphite, the injection is stopped and kept for a period of time to ensure that the phenolic resin enters the pores of the porous graphite as much as possible. Then the impregnation equipment is pressurized, and the pressurization is stopped when the pressure rises to 5MPa. After the excess liquid phenolic resin is discharged under the pressurized state, stirring is started and maintained for a period of time while maintaining the pressure of 5MPa. At this time, the high pressure directly acts on the liquid resin on the surface of the bonding graphite particles due to the discharge of excess liquid resin, which is beneficial to the impregnation of the liquid phenolic resin. In addition, the stirring process can effectively increase the contact between the graphite matrix and the surface of the phenolic resin, which is beneficial to accelerate the further impregnation of the liquid phenolic resin.
[0074] The carbonization temperature in step (IV) is 1000-1300°C. As an example, the maximum temperature may be, but is not limited to, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1250°C, and 1300°C. The carbonization is a gradient carbonization, wherein the temperature is first increased to 200-400°C at a rate of 8-15°C / min and then kept at this temperature for 1.0-4.0h, and then increased to 800-1000°C at a rate of 2-8°C / min and then kept at this temperature for 0.5-2.0h.
[0075] The pressure used in the medium static pressure treatment in step (V) is 100-170 MPa. As an example, the pressure can be, but is not limited to, 100 MPa, 110 MPa, 120 MPa, 130 MPa, 140 MPa, 150 MPa, 160 MPa, and 170 MPa. Post-treatment includes breaking up, demagnetizing, and screening. The breaking up equipment can be rod grinding, breaking up to a Dv50 of 10-15 μm, and the mesh number used for screening is 325 mesh.
[0076] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention. The embodiments of the present invention include an explanation of the technical scheme of the artificial graphite material and an explanation of the technical scheme of the preparation method of the artificial graphite material.
[0077] Example 1
[0078] This embodiment is a method for preparing an artificial graphite material, which includes the following steps.
[0079] (I) Pretreatment of porous graphite
[0080] The porous graphite (with a total pore volume of 0.052 cm 3 / g, micropore volume is 0.0017cm 3 / g, micropore volume accounts for 3.27%, particle size is about 5cm, graphitization degree is 94%, specific surface area is 12.1m 2 / g, tap density is 0.72g / cm 3 , compacted density is 1.65g / cm 3 , the first coulomb efficiency is 84.3%) to be coarsely crushed to a particle size of 55 mm, and then finely crushed to a particle size of 12 μm by a mechanical grinder, and the crushed porous graphite is shaped to obtain a graphite matrix.
[0081] (II) Preparation of phenolic resin
[0082] Phenol and ethylenediamine (2% of the mass of phenol) were stirred in a magnetic stirring water bath for 30 minutes, and then heated to 80°C for stirring. Formaldehyde was added dropwise to phenol during the stirring process, and the molar ratio of formaldehyde to phenol was 1.2:1. After the phenol was added dropwise, NaOH (3% of the mass of phenol) was added and stirred for 1 hour for secondary catalysis to obtain phenolic resin (viscosity at room temperature was 378mPa.s and coking value was 67%). Sodium dodecylbenzene sulfonate was added to the phenolic resin, and the mass ratio of sodium dodecylbenzene sulfonate to phenolic resin was 1:1000. After stirring for 30 minutes, micellar phenolic resin (viscosity at room temperature was 151mPa.s and coking value was 67%) was obtained.
[0083] (III) Place the graphite matrix in the impregnation tank, then reduce the air pressure to -0.08MPa and maintain it for 1 hour to ensure that the air in the pores of the graphite matrix is discharged as much as possible. Inject the micellar phenolic resin into the kneader under negative pressure. When the micellar phenolic resin completely infiltrates the graphite matrix, stop injecting and maintain it for 30 minutes. Then pressurize the impregnation equipment. When the pressure rises to 5MPa, stop pressurizing. Excess phenolic resin is discharged under pressure, and stirred for 1 hour while maintaining the pressure of 5MPa. After stirring for 1 hour, heat it to 300℃ at a rate of 5℃ / min and keep it warm for 2 hours. Then heat it to 600℃ at a rate of 3℃ / min and keep it warm for 5 hours to remove the volatiles of the resin. Finally, cool it in the furnace to obtain the precursor.
[0084] (IV) The precursor is placed in a box furnace, and the temperature is increased to 300°C at a rate of 10°C / min and kept at this temperature for 2 h. The temperature is then increased to 1000°C at a rate of 5°C / min and kept at this temperature for 1 h. Finally, the temperature is increased to 1150°C at a rate of 2°C / min and kept at this temperature for 2 h. The temperature is then decreased along with the furnace to obtain a primary material.
[0085] (V) The primary material is subjected to isostatic pressing at a pressure of 150 MPa and a holding time of 5 min. After isostatic pressing, the material is broken up to a Dv50 of 13 μm, and then demagnetized and sieved to obtain an artificial graphite material.
[0086] Example 2
[0087] This embodiment is a method for preparing an artificial graphite material, which includes the following steps.
[0088] (I) Pretreatment of porous graphite
[0089] The porous graphite (with a total pore volume of 0.038 cm2) was crushed by a jaw crusher. 3 / g, micropore volume is 0.0012cm 3 / g, micropore volume accounts for 3.16%, particle size is about 7cm, graphitization degree is 95%, specific surface area is 14.5m 2 / g, tap density is 0.65g / cm 3 , compacted density is 1.62g / cm 3 , the first coulomb efficiency is 82%) to be coarsely crushed to a particle size of 45 mm, and then finely crushed to a particle size of 10 μm by a mechanical grinder, and the crushed porous graphite is shaped to obtain a graphite matrix.
[0090] (II) Preparation of phenolic resin
[0091] Phenol and triethylamine (4% of the mass of phenol) were stirred in a magnetic stirring water bath for 25 minutes, and then heated to 90°C for stirring. Formaldehyde was added dropwise to phenol during the stirring process, and the molar ratio of formaldehyde to phenol was 1.3:1. After the phenol was added dropwise, NaOH (2% of the mass of phenol) was added and stirred for 2 hours for secondary catalysis to obtain phenolic resin (viscosity at room temperature was 370mPa.s and coking value was 70%). Sodium hexadecyl sulfonate was added to the phenolic resin, and the mass ratio of sodium hexadecyl sulfonate to phenolic resin was 1:900. After stirring for 45 minutes, micellar phenolic resin (viscosity at room temperature was 148mPa.s and coking value was 70%) was obtained.
[0092] (III) Place the graphite matrix in the impregnation tank, then reduce the air pressure to -0.08MPa and maintain it for 0.5h to ensure that the air in the pores of the graphite matrix is exhausted as much as possible. Inject the micellar phenolic resin into the kneader under negative pressure. When the micellar phenolic resin completely infiltrates the graphite matrix, stop injecting and maintain it for 30min. Then pressurize the impregnation equipment. When the pressure rises to 5MPa, stop pressurizing. Excess phenolic resin is discharged under pressure and stirred for 2h while maintaining the pressure at 5MPa. After stirring for 2h, heat to 400℃ at a rate of 8℃ / min and keep it warm for 1h. Then heat to 700℃ at a rate of 2℃ / min and keep it warm for 4h to remove the volatiles of the resin. Finally, cool it in the furnace to obtain the precursor.
[0093] (IV) The precursor is placed in a box furnace, and the temperature is increased to 400°C at a rate of 15°C / min and kept at this temperature for 3 h. The temperature is then increased to 950°C at a rate of 3°C / min and kept at this temperature for 2 h. Finally, the temperature is increased to 1100°C at a rate of 4°C / min and kept at this temperature for 3 h. The temperature is then decreased along with the furnace to obtain the initial material.
[0094] (V) The primary material is subjected to isostatic pressing treatment, the isostatic pressing pressure is 170 MPa, the pressure holding time is 4 minutes, and after isostatic pressing, it is broken up to a Dv50 of 12 μm, and then demagnetized and sieved to obtain artificial graphite material.
[0095] Example 3
[0096] This embodiment is a method for preparing an artificial graphite material, which includes the following steps.
[0097] (I) Pretreatment of porous graphite
[0098] The porous graphite (with a total pore volume of 0.065 cm 3 / g, micropore volume is 0.0025cm 3 / g, micropore volume accounts for 3.85%, particle size is about 7cm, graphitization degree is 93%, specific surface area is 14.0m 2 / g, tap density is 0.72g / cm 3 , compacted density is 1.64g / cm 3 , the first coulomb efficiency is 82%) to be coarsely crushed to a particle size of 75 mm, and then finely crushed to a particle size of 10 μm by a mechanical grinder, and the crushed porous graphite is shaped to obtain a graphite matrix.
[0099] (II) Preparation of phenolic resin
[0100] Phenol and triethanolamine (5% of the mass of phenol) were stirred in a magnetic stirring water bath for 40 minutes, and then heated to 95°C for stirring. Formaldehyde was added dropwise to phenol during the stirring process, and the molar ratio of formaldehyde to phenol was 1.1:1. After the phenol was added dropwise, NaOH (2% of the mass of phenol) was added and stirred for 0.5h for secondary catalysis to obtain phenolic resin (viscosity at room temperature was 372mPa.s and coking value was 73%). Sodium dodecyl sulfate was added to the phenolic resin, and the mass ratio of sodium dodecyl sulfate to phenolic resin was 1:1100. After stirring for 50 minutes, micellar phenolic resin (viscosity at room temperature was 144mPa.s and coking value was 73%) was obtained.
[0101] (III) Place the graphite matrix in the impregnation tank, then reduce the air pressure to -0.08MPa and maintain it for 0.5h to ensure that the air in the pores of the graphite matrix is discharged as much as possible. Inject the micellar phenolic resin into the kneader under negative pressure. When the micellar phenolic resin completely infiltrates the graphite matrix, stop injecting and maintain it for 60min. Then pressurize the impregnation equipment. When the pressure rises to 5MPa, stop pressurizing. Excess phenolic resin is discharged under pressure, and the pressure is kept at 5MPa for 1h. After stirring for 1h, heat it to 250℃ at a rate of 4℃ / min and keep it warm for 3h. Heat it to 800℃ at a rate of 4℃ / min and keep it warm for 8h to remove the volatiles of the resin. Finally, cool it in the furnace to obtain the precursor.
[0102] (IV) The precursor is placed in a box furnace, and the temperature is increased to 350°C at a rate of 12°C / min and kept at this temperature for 3 h. The temperature is then increased to 950°C at a rate of 5°C / min and kept at this temperature for 2 h. Finally, the temperature is increased to 1100°C at a rate of 2°C / min and kept at this temperature for 5 h. The temperature is then decreased along with the furnace to obtain the initial material.
[0103] (V) The primary material is subjected to isostatic pressing treatment, the isostatic pressing pressure is 120 MPa, the pressure holding time is 10 min, and after isostatic pressing, it is broken up to a Dv50 of 13 μm, and then demagnetized and sieved to obtain an artificial graphite material.
[0104] Example 4
[0105] This embodiment is a method for preparing an artificial graphite material, which includes the following steps.
[0106] (I) Pretreatment of porous graphite
[0107] The porous graphite (with a total pore volume of 0.052 cm 3 / g, micropore volume is 0.0017cm 3 / g, micropore volume accounts for 3.27%, particle size is about 5cm, graphitization degree is 94%, specific surface area is 12.1m2 / g, tap density is 0.72g / cm 3 , compacted density is 1.65g / cm 3 , the first coulomb efficiency is 84.3%) to be coarsely crushed to a particle size of 55 mm, and then finely crushed to a particle size of 12 μm by a mechanical grinder, and the crushed porous graphite is shaped to obtain a graphite matrix.
[0108] (II) Preparation of phenolic resin
[0109] Phenol and ethylenediamine (accounting for 2% of the mass of phenol) were stirred in a magnetic stirring water bath for 30 minutes, and then heated to 80°C for stirring. Formaldehyde was added dropwise to phenol during the stirring process, and the molar ratio of formaldehyde to phenol was 1.2:1. After the phenol was added dropwise, NaOH (accounting for 3% of the mass of phenol) was added and stirred for 1 hour for secondary catalysis to obtain phenolic resin (viscosity at room temperature was 378mPa.s and coking value was 67%).
[0110] (III) Place the graphite matrix in the impregnation tank, then reduce the air pressure to -0.08MPa and maintain it for 1 hour to ensure that the air in the pores of the graphite matrix is discharged as much as possible. Inject the phenolic resin into the kneader under negative pressure. When the phenolic resin completely infiltrates the graphite matrix, stop injecting and maintain it for 30 minutes. Then pressurize the impregnation equipment. When the pressure rises to 5MPa, stop pressurizing. Excess phenolic resin is discharged under pressure, and the pressure is kept at 5MPa for 1 hour. After stirring for 1 hour, heat it to 300℃ at a rate of 5℃ / min and keep it warm for 2 hours. Then heat it to 600℃ at a rate of 3℃ / min and keep it warm for 5 hours to remove the volatiles of the resin. Finally, cool it in the furnace to obtain the precursor.
[0111] (IV) The precursor is placed in a box furnace, and the temperature is increased to 300°C at a rate of 10°C / min and kept at this temperature for 2 h. The temperature is then increased to 1000°C at a rate of 5°C / min and kept at this temperature for 1 h. Finally, the temperature is increased to 1150°C at a rate of 2°C / min and kept at this temperature for 2 h. The temperature is then decreased along with the furnace to obtain a primary material.
[0112] (V) The primary material is subjected to isostatic pressing at a pressure of 150 MPa and a holding time of 5 min. After isostatic pressing, the material is broken up to a Dv50 of 13 μm, and then demagnetized and sieved to obtain an artificial graphite material.
[0113] Comparative Example 1
[0114] This comparative example is a method for preparing an artificial graphite material, which comprises the following steps.
[0115] (I) Pretreatment of porous graphite
[0116] The porous graphite (with a total pore volume of 0.052 cm 3 / g, micropore volume is 0.0017cm 3 / g, micropore volume accounts for 3.27%, particle size is about 5cm, graphitization degree is 94%, specific surface area is 12.1m 2 / g, tap density is 0.72g / cm 3 , compacted density is 1.65g / cm 3 , the first coulomb efficiency is 84.3%) to be coarsely crushed to a particle size of 55 mm, and then finely crushed to a particle size of 12 μm by a mechanical grinder, and the crushed porous graphite is shaped to obtain a graphite matrix.
[0117] (II) The graphite substrate is placed in a box furnace, heated to 300°C at a rate of 10°C / min and kept at this temperature for 2 h, then heated to 1000°C at a rate of 5°C / min and kept at this temperature for 1 h, and finally heated to 1150°C at a rate of 2°C / min and kept at this temperature for 2 h, then cooled with the furnace, broken up to a Dv50 of 13 μm, and then demagnetized and sieved to obtain artificial graphite material.
[0118] Comparative Example 2
[0119] This comparative example is a method for preparing an artificial graphite material, which comprises the following steps.
[0120] (I) Pretreatment of porous graphite
[0121] The porous graphite (with a total pore volume of 0.052 cm 3 / g, micropore volume is 0.0017cm 3 / g, micropore volume accounts for 3.27%, particle size is about 5cm, graphitization degree is 94%, specific surface area is 12.1m 2 / g, tap density is 0.72g / cm 3 , compacted density is 1.65g / cm 3 , the first coulomb efficiency is 84.3%) to be coarsely crushed to a particle size of 55 mm, and then finely crushed to a particle size of 12 μm by a mechanical grinder, and the crushed porous graphite is shaped to obtain a graphite matrix.
[0122] (II) The graphite substrate is placed in a box furnace, and the temperature is increased to 300°C at a rate of 10°C / min and kept at this temperature for 2 h. The temperature is then increased to 1000°C at a rate of 5°C / min and kept at this temperature for 1 h. Finally, the temperature is increased to 1150°C at a rate of 2°C / min and kept at this temperature for 2 h. The temperature is then decreased along with the furnace to obtain a primary material.
[0123] (III) The primary material is subjected to isostatic pressing at a pressure of 150 MPa and a holding time of 5 min. After isostatic pressing, the material is broken up to a Dv50 of 13 μm, and then demagnetized and sieved to obtain an artificial graphite material.
[0124] Comparative Example 3
[0125] This comparative example is a method for preparing an artificial graphite material, which comprises the following steps.
[0126] (I) Pretreatment of porous graphite
[0127] The porous graphite (with a total pore volume of 0.052 cm 3 / g, micropore volume is 0.0017cm 3 / g, micropore volume accounts for 3.27%, particle size is about 5cm, graphitization degree is 94%, specific surface area is 12.1m 2 / g, tap density is 0.72g / cm 3 , compacted density is 1.65g / cm 3 , the first coulomb efficiency is 84.3%) to be coarsely crushed to a particle size of 55 mm, and then finely crushed to a particle size of 12 μm by a mechanical grinder, and the crushed porous graphite is shaped to obtain a graphite matrix.
[0128] (II) Preparation of phenolic resin
[0129] Phenol and sodium hydroxide (5% by mass of phenol) were stirred in a magnetic stirring water bath for 30 minutes, and then heated to 80°C for stirring. Formaldehyde was added dropwise to phenol during stirring, and the molar ratio of formaldehyde to phenol was 1.2:1, to obtain phenolic resin (viscosity at room temperature was 1002 mPa.s, and coking value was 59%).
[0130] (III) Place the graphite matrix in the impregnation tank, then reduce the air pressure to -0.08MPa and maintain it for 1 hour to ensure that the air in the pores of the graphite matrix is discharged as much as possible. Inject the phenolic resin into the kneader under negative pressure. When the phenolic resin completely infiltrates the graphite matrix, stop injecting and maintain it for 30 minutes. Then pressurize the impregnation equipment. When the pressure rises to 5MPa, stop pressurizing. Excess phenolic resin is discharged under pressure, and the pressure is kept at 5MPa for 1 hour. After stirring for 1 hour, heat it to 300℃ at a rate of 5℃ / min and keep it warm for 2 hours. Then heat it to 600℃ at a rate of 3℃ / min and keep it warm for 5 hours to remove the volatiles of the resin. Finally, cool it in the furnace to obtain the precursor.
[0131] (IV) The precursor is placed in a box furnace, heated to 300°C at a rate of 10°C / min and kept at this temperature for 2 h, then heated to 1000°C at a rate of 5°C / min and kept at this temperature for 1 h, and finally heated to 1150°C at a rate of 2°C / min and kept at this temperature for 2 h, then cooled with the furnace, broken up to a Dv50 of 13 μm, and then demagnetized and sieved to obtain artificial graphite material.
[0132] Comparative Example 4
[0133] This comparative example is a method for preparing an artificial graphite material, which comprises the following steps.
[0134] (I) Pretreatment of porous graphite
[0135] The porous graphite (with a total pore volume of 0.052 cm 3 / g, micropore volume is 0.0017cm 3 / g, micropore volume accounts for 3.27%, particle size is about 5cm, graphitization degree is 94%, specific surface area is 12.1m 2 / g, tap density is 0.72g / cm 3 , compacted density is 1.65g / cm 3 , the first coulomb efficiency is 84.3%) to be coarsely crushed to a particle size of 55 mm, and then finely crushed to a particle size of 12 μm by a mechanical grinder, and the crushed porous graphite is shaped to obtain a graphite matrix.
[0136] (II) Preparation of phenolic resin
[0137] Phenol and ethylenediamine (accounting for 2% of the mass of phenol) were stirred in a magnetic stirring water bath for 30 minutes, and then heated to 80°C for stirring. Formaldehyde was added dropwise to phenol during the stirring process, and the molar ratio of formaldehyde to phenol was 1.2:1. After the phenol was added dropwise, NaOH (accounting for 3% of the mass of phenol) was added and stirred for 1 hour for secondary catalysis to obtain phenolic resin (viscosity at room temperature was 378mPa.s and coking value was 67%).
[0138] (III) Place the graphite matrix in the impregnation tank, then reduce the air pressure to -0.08MPa and maintain it for 1 hour to ensure that the air in the pores of the graphite matrix is discharged as much as possible. Inject the phenolic resin into the kneader under negative pressure. When the phenolic resin completely infiltrates the graphite matrix, stop injecting and maintain it for 30 minutes. Then pressurize the impregnation equipment. When the pressure rises to 5MPa, stop pressurizing. Excess phenolic resin is discharged under pressure, and the pressure is kept at 5MPa for 1 hour. After stirring for 1 hour, heat it to 300℃ at a rate of 5℃ / min and keep it warm for 2 hours. Then heat it to 600℃ at a rate of 3℃ / min and keep it warm for 5 hours to remove the volatiles of the resin. Finally, cool it in the furnace to obtain the precursor.
[0139] (IV) The precursor is placed in a box furnace, heated to 300°C at a rate of 10°C / min and kept at this temperature for 2 h, then heated to 1000°C at a rate of 5°C / min and kept at this temperature for 1 h, and finally heated to 1150°C at a rate of 2°C / min and kept at this temperature for 2 h, then cooled with the furnace, broken up to a Dv50 of 13 μm, and then demagnetized and sieved to obtain artificial graphite material.
[0140] Comparative Example 5
[0141] This embodiment is a method for preparing an artificial graphite material, which includes the following steps.
[0142] (I) Pretreatment of porous graphite
[0143] The porous graphite (with a total pore volume of 0.052 cm 3 / g, micropore volume is 0.0017cm 3 / g, micropore volume accounts for 3.27%, particle size is about 5cm, graphitization degree is 94%, specific surface area is 12.1m 2 / g, tap density is 0.72g / cm 3 , compacted density is 1.65g / cm 3 , the first coulomb efficiency is 84.3%) to be coarsely crushed to a particle size of 55 mm, and then finely crushed to a particle size of 12 μm by a mechanical grinder, and the crushed porous graphite is shaped to obtain a graphite matrix.
[0144] (II) Preparation of phenolic resin
[0145] Phenol and sodium hydroxide (5% by mass of phenol) were stirred in a magnetic stirring water bath for 30 minutes, and then heated to 80°C for stirring. Formaldehyde was added dropwise to phenol during stirring, and the molar ratio of formaldehyde to phenol was 1.2:1, to obtain phenolic resin (viscosity at room temperature was 1002 mPa.s, and coking value was 59%).
[0146] (III) Place the graphite matrix in the impregnation tank, then reduce the air pressure to -0.08MPa and maintain it for 1 hour to ensure that the air in the pores of the graphite matrix is discharged as much as possible. Inject the phenolic resin into the kneader under negative pressure. When the phenolic resin completely infiltrates the graphite matrix, stop injecting and maintain it for 30 minutes. Then pressurize the impregnation equipment. When the pressure rises to 5MPa, stop pressurizing. Excess phenolic resin is discharged under pressure, and the pressure is kept at 5MPa for 1 hour. After stirring for 1 hour, heat it to 300℃ at a rate of 5℃ / min and keep it warm for 2 hours. Then heat it to 600℃ at a rate of 3℃ / min and keep it warm for 5 hours to remove the volatiles of the resin. Finally, cool it in the furnace to obtain the precursor.
[0147] (IV) The precursor is placed in a box furnace, and the temperature is increased to 300°C at a rate of 10°C / min and kept at this temperature for 2 h. The temperature is then increased to 1000°C at a rate of 5°C / min and kept at this temperature for 1 h. Finally, the temperature is increased to 1150°C at a rate of 2°C / min and kept at this temperature for 2 h. The temperature is then decreased along with the furnace to obtain a primary material.
[0148] (V) The primary material is subjected to isostatic pressing at a pressure of 150 MPa and a holding time of 5 min. After isostatic pressing, the material is broken up to a Dv50 of 13 μm, and then demagnetized and sieved to obtain an artificial graphite material.
[0149] The artificial graphite materials prepared in Examples 1 to 4 and Comparative Examples 1 to 5 were tested by nitrogen isothermal adsorption-desorption curve to obtain specific surface area, pore volume and pore size distribution curve. The tap density was tested by a tap density meter. The compacted density was tested by a powder compaction density meter.
[0150] The artificial graphite materials prepared in Examples 1 to 4 and Comparative Examples 1 to 5 were used as active materials, mixed with a water dispersion of a binder acrylonitrile multipolymer (LA132, solid content 15%) and a conductive agent (Super-P) in a mass ratio of 92:6:2, added with a certain amount of water as a solvent, homogenized, and the solid content of the slurry was adjusted to 55%, coated on copper foil, and vacuum dried and rolled to prepare a negative electrode sheet. The counter electrode was a metal lithium sheet, and the electrolyte was 1 mol / L LiPF 6 The solution (the solvent is a mixture of EC, DMC and EMC in a volume ratio of 1:1:1) and the separator is a polypropylene microporous membrane, which is assembled into a CR2032 button cell in a glove box filled with inert gas. The charge and discharge test of the button cell is carried out on the LANHE battery test system of LANHE Electronics Co., Ltd.
[0151] The first charge and discharge performance test: At room temperature, discharge at a constant current of 0.1C until the voltage reaches 0.01V, then discharge at a constant current of 0.02C until the voltage reaches 0.005V, and charge at a constant current of 0.1C until the voltage reaches 2.0V to obtain the first coulombic efficiency.
[0152] Table 1 Performance test results of artificial graphite materials obtained in Examples 1 to 4 and Comparative Examples 1 to 5
[0153]
[0154] The control group is a conventional artificial graphite with a particle size of 10 to 15 μm and a graphitization degree of 90 to 95%.
[0155] From the results in Table 1, it can be seen that the raw material used in the preparation method of the artificial graphite material of the present invention is porous graphite, and its total pore volume is more than 6 times that of conventional artificial graphite (control group). By improving the preparation process of phenolic resin to obtain phenolic resin with low viscosity and high coking value, the pores can be filled by combining vacuum impregnation process and adding isostatic pressing, and the porosity of the obtained artificial graphite material is only 0.006cm 3 / g, which is close to the porosity of conventional artificial graphite. Therefore, the preparation method of the present invention can greatly improve the use value of porous graphite, and can obtain higher compaction density, tap density and first efficiency, as well as low specific surface area.
[0156] Combining the comparison of Example 1 and Example 4, it can be seen that the micellar phenolic resin prepared by mixing the liquid phase phenolic resin with anionic surfactant can obtain higher compaction density, tap density and first effect, and lower viscosity. This is because the micelles will occupy a certain space in the liquid, producing a steric hindrance effect, which will hinder the mutual approach and entanglement between the phenolic resin molecules, making the flow of the liquid easier, thereby causing the viscosity of the phenolic resin to decrease. The reduction in the viscosity of the phenolic resin will further improve the effect of vacuum impregnation, thereby filling more pores.
[0157] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing an artificial graphite material, characterized in that: Includes steps: (I) Pretreatment of porous graphite The porous graphite is crushed and shaped to obtain a graphite matrix; (II) Preparation of phenolic resin Phenol and an organic base are mixed and heated, formaldehyde is added dropwise for reaction, and an inorganic base is added for further reaction to obtain a phenolic resin; (III) Impregnation Under vacuum conditions, the phenolic resin is impregnated into the graphite substrate and stirred under pressure for a certain period of time, and then heated to remove volatile components of the resin to obtain a precursor; (IV) Carbonization Carbonizing the precursor to obtain a primary material; (V) Isostatic Pressing The initial material is subjected to isostatic pressing and then to post-treatment.
2. The method for preparing the artificial graphite material according to claim 1, characterized in that: The invention comprises one of the following features (1) to (20): (1) The total pore volume of the porous graphite is 0.01 to 0.10 cm 3 / g, micropore volume is 0.0005~0.010cm 3 / g, micropore volume accounts for 0.5-10.0%, particle size is 3-8cm, and graphitization degree is 90-95%; (2) The specific surface area of the porous graphite is greater than 12.0 m 2 / g, tap density is 0.65~0.75g / cm 3 , compacted density ≤1.65g / cm 3 , the first coulombic efficiency ≤85%; (3) The pulverization includes coarse pulverization and fine pulverization, firstly coarse pulverization to a particle size of 1 to 100 mm, and then fine pulverization to a particle size of 10 to 15 μm; (4) The pulverization includes coarse crushing and fine crushing. The coarse crushing is carried out by a jaw crusher, and the fine crushing is carried out by a mechanical mill, a roller mill or a jet mill. (5) The main machine frequency of the shaping machine used in the shaping is 2 to 5 Hz, and the main machine classification frequency is 5 to 7 Hz; (6) The organic base comprises at least one of ethylenediamine, triethylamine and triethanolamine; (7) the organic base accounts for 1 to 5% of the mass of the phenol; (8) The heating temperature in step (II) is 50 to 100° C.; (9) The molar ratio of the formaldehyde to the phenol is 1.0 to 1.4:1; (10) The inorganic base comprises potassium hydroxide and / or sodium hydroxide; (11) the inorganic base accounts for 1 to 5% of the mass of the phenol; (12) The phenol and the organic base are stirred in a magnetic stirring water bath for 15 to 40 minutes; (13) stirring after adding the inorganic base, and the stirring time is 0.5 to 2.0 hours; (14) The viscosity of the phenolic resin at room temperature is ≤400 mPa.s and the coking value is ≥66%; (15) The maximum heating temperature in step (III) is 500 to 800° C.; (16) The heating in step (III) is stepwise heating, wherein the stepwise heating is firstly heated to 200-400°C at a rate of 2-8°C / min and then kept at that temperature for 1-4h, and then heated to 500-800°C at a rate of 2-5°C / min and then kept at that temperature for 3-10h; (17) The carbonization temperature is 1000-1300° C.; (18) The carbonization is a gradient carbonization, wherein the temperature is first increased to 200-400°C at a rate of 8-15°C / min and then kept at this temperature for 1.0-4.0h, then increased to 800-1000°C at a rate of 2-8°C / min and then kept at this temperature for 0.5-2.0h, and finally increased to 1050-1200°C at a rate of 1-5°C / min and then kept at this temperature for 1.0-5.0h; (19) The pressure used in the isostatic pressing treatment is 100 to 170 MPa; (20) The post-processing includes breaking up, demagnetizing and screening.
3. The method for preparing the artificial graphite material according to claim 1, characterized in that: Before the phenolic resin is impregnated into the graphite matrix, the phenolic resin and anionic surfactant are mixed to obtain micellar phenolic resin.
4. The method for preparing the artificial graphite material according to claim 3, characterized in that: The anionic surfactant includes at least one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfonate, sodium dodecyl sulfate, and sodium hexadecyl sulfonate. The mass ratio of the anionic surfactant to the phenolic resin is 1:800-1200.
5. The method for preparing the artificial graphite material according to claim 3, characterized in that: The micellar phenolic resin has a viscosity of ≤200 mPa.s at room temperature and a coking value of ≥66%.
6. The method for preparing the artificial graphite material according to claim 1, characterized in that: Before the phenolic resin is impregnated into the graphite substrate, the graphite substrate is placed in an impregnation tank and vacuumed to exhaust air in the pores of the graphite substrate.
7. The method for preparing the artificial graphite material according to claim 6, characterized in that: The vacuum is evacuated to a pressure of ≤-0.08 MPa, and the pressure is maintained for 0.5 to 1.0 h.
8. The method for preparing the artificial graphite material according to claim 1, characterized in that: The phenolic resin and the graphite matrix are impregnated in a kneader.
9. The method for preparing the artificial graphite material according to claim 8, characterized in that: The kneader is first pressurized to 3-8 MPa, then the pressurization is stopped and the pressure is kept constant and stirring is continued for 0.5-3.0 hours. The frequency of the kneader is 10-20 Hz.
10. The artificial graphite material prepared by the method for preparing an artificial graphite material according to any one of claims 1 to 9, characterized in that: Specific surface area ≤1.6m 2 / g, tap density is 0.95~1.10g / cm 3 , compacted density is 1.70~1.86g / cm 3 , the first coulombic efficiency is ≥92%.